Accumulation of Polycyclic Aromatic Hydrocarbon Content in Talinium Triangulare Grown in Spent Engine Oil Polluted Soil (International Journal of Latest Technology in Engineering Management & Applied Science, 2025)
Polycyclic Aromatic hydrocarbons constitute a large class of organic compound that are compose of two or more fused aromatic rings. They are mostly produced by the pyrolysis or incomplete combustion of organic materials. The level of polycyclic aromatic hydrocarbons (PAHs) were determined in spent motor-cycle engine oil, spent sport car engine oil, Talinium triangulare (water leaf) grown on soil contaminated with spent sport car engine oil, and spent motor-cycle oil. The PAHs were analyzed using gas chromatograph-Flame Ionation Detector (GC-FID). Additionally, the growth factors were established using Talinum Triangulare grown in the unpolluted soil and exposed to both spent sport car engine oil and motor-cycle oil. In terms of their bio-tolerance, the uncontaminated talinium triangulare displayed a superior growth performance in comparison to the exposed plant. Nonetheless, there was a notable difference between uncontaminated and contaminated plants (P<0.05). The PAHs results indicated that spent sport car engine oil had higher total PAHs concentration of 5.5518 mg/L than spent motor-cycle engine oil, which had a total PAHs concentration of 2.7490 mg/L. Talinium Triangulare grown on soil contaminated with spent sport car engine oil accumulated 0.9108 mg/kg of total PAHs, while spent motor-cycle oil accumulated a total PAHs concentration of 0.5276 mg/kg. In spent sport car engine oil benzo (b) flouoranthene had the highest concentration, while in spent motor-cycle engine oil, the highest concentration was benzo (a) pyrene. Out of the sixteen PAHs USEPA targets, kylene was the only one that wasn't found in any of the samples. These findings demonstrated the presence of hazardous PAHs in the spent engines oil of both motor-cycles and sport car, which are carelessly discarded into the environment and can bioaccumulate in edible plants. It implies that eating vegetables grown on soil tainted with used engine oil poses an inherent risk and danger to consumers.